1996
DOI: 10.1148/radiology.198.1.8539388
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal mucin-producing tumors of the pancreas: imaging findings.

Abstract: Imaging modalities, especially US and ERCP, enable early diagnosis of mucin-producing pancreatic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 0 publications
4
70
0
2
Order By: Relevance
“…On CT and sonography, the tumor appears as clustered small cystsor asa cystic lesionwith a lobulated or irregular marginandsparse septa, characteris tics that are often associated with dilatation of the pancreatic duct near the lesion [4,5].…”
mentioning
confidence: 99%
“…On CT and sonography, the tumor appears as clustered small cystsor asa cystic lesionwith a lobulated or irregular marginandsparse septa, characteris tics that are often associated with dilatation of the pancreatic duct near the lesion [4,5].…”
mentioning
confidence: 99%
“…CT scanning was performed in 69 patients with a single-detector row helical CT scanner (HiS- However, more recent studies have found that CT and MRI have diagnostic accuracies ranging from 27% to 96.8% in detecting pancreatic cystic neoplasms, which were lower than expected (13)(14)(15). Although imaging findings and differentiation of pancreatic cystic neoplasms have been reported in many studies, their accurate radiologic differentiation is still difficult due to their overlapping morphologies and their very small sizes for evaluation (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…the identification of vascularized inclusions (Figure 4), and for the differential diagnosis between MCA and a pseudocyst [17,46] . IPMNs are cystic tumors of the pancreas recently reported with increasing frequency [6,38,41,47,48] . They are macroscopically characterized by having an intraductal origin and growth [49] , with the production of dense mucin that fills the main pancreatic duct (the ductectatic mucin-hypersecreting variant) or with endoluminal papillary proliferation (the papillary-villous variant).…”
Section: Mucinous Cystic Tumorsmentioning
confidence: 99%